Pendampingan Belajar Anak yang Berkonflik dengan Hukum Berbasis Mathematics Adventure in Dayak Kalimantan Tengah: Learning Assistance for Children in Conflict with the Law Based on Mathematics Adventure in Dayak, Central Kalimantan - Ratnawati, Oktaviana Ainun; Mairing, Jackson Pasini; Artuti, Emy; Pancarita, Pancarita; Rizaldi, Muhammad; Ngadi, Ngadi (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
This PkM activity aims to accompany teaching and learning activities at LPKA targeting assisted students who are serving a prison term so they cannot go to school like their peers. Based on data from interviews with one of the sources who is the Person in Charge of the Development Division of LPKA Tjilik Riwut, Central Kalimantan, it is stated that child conflict -The majority of children serving criminal terms are perpetrators of sexual abuse, murder, and several children are involved in theft cases. PkM activities last for 3 months with a total of 7 learning meetings with a total number of students varying from 27 – 35 students each week. Each meeting is filled with mathematics learning that is appropriate to the context of daily life on number operations; distance, speed, time; social arithmetic; and the volume of the space. Learning about local culture is also provided by introducing each district in Central Kalimantan. The good response given by the LPKA and the assisted students who felt the benefits of the PkM program stated that this program was truly called Devotion because the LPKA felt helped in fulfilling the learning materials and the assisted students also felt happy taking part in the learning.